(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The work was carried out at the clinical base of the Bukhara State Medical Institute - and at the regional multidisciplinary clinical hospital. Analyzed data of examination and treatment of 75 patients from 18 to 60 years old, with ENT pathology against the background of HIV infection for the period from 2020-2021. All patients underwent a comprehensive examination, including otorhinolaryngological, clinical laboratory, bacteriological studies. The results of the study showed that the main causative agents of middle ear disease developed against the background of HIV infection, the pathogenic microflora in the group of HIV-infected patients was significantly higher compared to similar non-HIV-infected patients.